Effects of Multicomponent Physical Exercise Programs on Physical Fitness in People with Intellectual Disabilities: A Systematic Review - Cofre-Bolados, C; De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
People with intellectual disabilities (ID) have high rates of overweight and obesity, heart and metabolic diseases, and low motor development. These factors compromise functional independence and autonomy in activities of daily living. The objective of this study was to clarify the design and implementation of multicomponent physical exercise programs (MPEPs) and evaluate their effects on physical fitness in people with ID. A search for scientific articles in English published before 2022 was conducted using Web of Science, PubMed, Scopus, and Science Direct databases. Scientific papers describing the effects of MPEPs on physical fitness in people with ID were considered. A total of 374 articles involving people with ID were included. Positive physical fitness outcomes were found in interventions with MPEPs in its morphological components and to a lesser extent in the motor, muscular, metabolic, and cardiorespiratory aspects in people with ID. Further research is needed to standardize and elucidate the effects of the MPEP on other functional dimensions of physical fitness to use them as a physical activity alternative to reduce sedentary behavior in people with ID. © 2022 by the authors.